An ontology-driven knowledge graph for tourism information management [version 2; peer review: 1 approved, 2 approved with reservations] - Mayukh Bagchi; SUBHASHIS DAS (Open Research Europe)
Background Lao Tzu, the ancient Chinese philosopher, had famously said, “a journey of a thousand miles begins with a single step”. The modern ecosystem of tourism is extremely multi-faceted and multi-context dependent, so much so that tourists, planning on an excursion, have an entire range of queries from as basic as “Where to eat?” to as complex as “List all the eating establishments which are suitable for groups and also provide children menu”. Such a list becomes even more complicated due to the intermixing of different perceptions, languages, cultures and economies in which tourists are enmeshed in. Accordingly, such increasing complexity in questions from tourists necessitate the need to provide specialized and fine-grained data and information services which are beyond the Information and communications technology (ICT) infrastructures in vogue in tourism today. Methods In this paper, we propose and advocate the use of, via a theoretically and implementationally well-founded methodology, the Artificial Intelligence (AI) backed technology of ontology-driven Knowledge Graphs, to provide fine-grained information services to tourists at any scale and at any level of complexity. Results and Conclusions The methodology is validated by developing a fully populated tourism-specific ontology-driven knowledge graph having 4264 RDF statements and ready for reuse, extension and exploitation as a part of any of the current ICT infrastructure in tourism sector.